A RANDOMIZED TRIAL TO STUDY THE COMPARISON OF TRIGGER POINT DRY NEEDLING VERSUS KINESIO TAPING TECHNIQUE IN MYOFASCIAL PAIN SYNDROME DURING A 3-MONTH FOLLOW UP (International Journal of Physiotherapy, 2016)
Background: Managemen of myofascial pain syndrome (MPS) is a current research subject since there is a small number of randomized studies comparing different management techniques. Multiple studies attempted to assess various treatment options including trigger point dry needling and kinesiotaping. We compared the effects of trigger point dry needling and kinesiotaping in the management of myofascial pain syndome during a 3-month follow-up period.Methods: In this prospective randomized studyin MPS patients with upper trapezius muscle trigger points, the effects of dry needling (n=28) and kinesiotaping (n=27) was compared with regard to the visual analog scale (VAS), neck disability index (NDI), and Nottingham health profile (NHP) scores measured at the weeks 0, 4, and 12.Results: Both dry needling and kinesiotaping comparably reduced VAS scores measured at the weeks 4 and 12 and their efficacies were more remarkable at the week 12 (p